Analysis of the thickness of layered armor to provide protection against 7.62 mm ball projectiles using experimental and numerical methods - Morghode, Divyanshu S.; Thakur, D. G.; Salunkhe, Sachin; Cepova, Lenka; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
The layered configuration of different material plates is one of the ways of achieving protection against different kinds of kinetic energy ammunitions. The thickness of each plate is one of the most important influencing parameters to prevent the penetration of the projectile. In the present study, a layered configuration of the Al2O3 and Al 7075-T651 is analysed, to prevent the perforation of 7.62 mm Lead core projectile, under normal impact conditions, by using LS-DYNA numerical simulations. Experiments were conducted on Al 7075-T651 plate and Numerical model was validated with experiment results. To achieve the objective, the validated numerical model was used to investigate influence on various Al2O3 and Al 7075-T651 combinations. Three factors led to the selection of Al 7075-T561 and Al2O3 as the target materials. First, the literature review revealed that these materials have already been employed in the construction of armour. Second, Al2O3 is a brittle material whereas Al 7075-T651 is ductile. Consequently, when combined in a layered arrangement, these materials offer the ideal destroyer-absorber arrangement. Thirdly, these materials have lower densities than steel. As a result, these materials offer a lightweight alternative for lead core 7.62 mm bullet defense. From the analysis, it is observed that two layered configurations were found to be effective in the prevention of bullet perforation: a front plate of Al2O3 that was 10 mm thick and had a rear plate of Al 7075-T651 that was 06 mm thick, and a front plate of Al2O3 that was 04 mm thick and had a 12 mm thick layer of Al 7075-T651.